Thyroid disorders in Hepatitis C virus infected untreated patients - Muhammad Adnan Saeed , Muhammad Sadiq , Asim Zulfiqar , Javed Irfan , Samina Jalali (Journal of Rawalpindi Medical College, 2009)
Background: To determine the association of thyroid disorders with chronic hepatitis C virus infection in patients who are not getting any antiviral treatment. Methods: Fifty patients without pre-existing thyroid abnormality having positive Hepatitis C Virus (HCV) infection (confirmed on PCR) and not willing for getting anti-viral treatment (interferon) were included in the study. Blood samples from 50 patients were collected at base line, 03 months, 06 months, 09 months and at 12 months. The level of thyroid stimulating hormone (TSH) and thyroid antibodies was measured in these samples. Results: Eleven patients (22%) developed thyroid disorder during the study period. Majority of the patients (73%) developed thyroid disorder on the basis of change in TSH level whereas 18% developed thyroid disorder on the basis of alteration in thyroid antibodies levels and 9% patients abnormality both in TSH levels and change in thyroid antibody titre. Conclusion: A close association of thyroid disorder and chronic HCV infection is noted in the study population.